Enhancing Vocabulary Instruction through Strategic Media Integration: A Case Study on Media Utilization at Tertiary Level - Faridawati, Faridawati; Lisna, Lisna; Nasrullah, Rahmat (LP3M, Universitas Muhammadiyah Kendari, 2024)
Media utilization plays a crucial role in enhancing the teaching and learning process within the classroom environment. This study investigates how a lecturer at Universitas Muhammadiyah Kendari perceives the use of teaching media in vocabulary instruction. Utilizing a qualitative descriptive approach through a case study, the research involved one lecturer and data collected from three classroom observations and two interviews. The analysis employed thematic coding across six key aspects: purpose, media selection, utilization, benefits, challenges, and effectiveness. The findings indicate that the lecturer employed a diverse range of teaching media, with multimedia resources, such as audio-books, being particularly prominent due to their integration of both audio and visual elements. Interviews data corroborates this observation, revealing the lecturer's belief that selecting appropriate media significantly enhances student engagement and aids in achieving learning objectives. Additionally, the study highlights that integrating various media types fosters a more interactive and dynamic vocabulary learning environment. The results further suggest that the lecturer demonstrates a robust understanding of media utilization, as evidenced by the absence of significant challenges in the process. Overall, the study underscores the effectiveness of diverse media in enriching vocabulary instruction and suggests that strategic media integration can greatly enhance the learning experience.